MEWUJUDKAN KARAKTER GENERASI MUDA BERWAWASAN KEBANGSAAN MELALUI PENDIDIKAN ADAPTIF (STUDI KASUS DI SMPN 2 TEMPURAN) - Muliani; Kuntarti, Rita; Hanry Putrantono, Asep; Murtopo, Adi (PPM Sdirjianbang Akademi Militer, 2024)
The progress of a nation or a country can be measured through the education. The education is crucial since it will create produce skilled human resources which have intellectual capabilities as well as high spiritual and emotional. Education is a planned attempt in the process of guidance and learning for the young generation to develop and grow as an independent, responsible, creative, knowledgeable, healthy, and noble human being physically or spiritually. Education and character training have a huge role in the civilization advancement for Indonesia to become an increasingly advanced nation and as better human resources, perceptive , and caracterized global competitiveness country. This research aims to understand the pattern, the inhibitor factors and the endeavour of the character building education in SMPN 2 Tempuran (Junior High School State 2 Termpuran). It was using qualitative descriptive research, which used data gathering through interviews and documentation studies.This research population is SMPN 2 Tempuran students and the samples were taken in IX C class. The sample class was considered based on the student condition of the class because it has many cases. The studies show that character education is not only instills the student's morals but rather strengthens personal development in various aspects. This includes personality development, responsibility, honestly, discipline, caring and having empathy to others. The main factor in educational character is family. On the other hand, barrier factor comes from student intercommunication. The school works in embedding characterized national insight mindset by holding the Regional Leaders Coordination Forum (FORKOMPIMDA) and the community. Expressing firm punishment and followed by school, family and society collaboration have become very important in promoting holistic character development .